BEARING CAPACITY AND SETTLEMENT BEHAVIOUR OF COASTAL SOIL FOR THE PLANNED BALONGAN PORT DEVELOPMENT, WEST JAVA - Ekasara, Adam Raka; Raharjo, Purnomo; Susilowati, Susilowati (Marine Geological Institute of Indonesia, 2025)
The planned development of Balongan Port in West Java requires a comprehensive geotechnical evaluation to support foundation planning at the proposed site, which is underlain by soft, clay-rich sediments. This study aims to assess the bearing capacity of the subsurface and predict potential settlement behaviour by integrating field and laboratory investigations. Standard Penetration Test (SPT) data from two boreholes, BH-3 (14 m) and BH-4 (18 m), and were complemented by laboratory analyses of soil physical and mechanical properties. The site is primarily composed of high-plasticity clay, known for its low strength, high compressibility, and variable geotechnical characteristics. Calculations based on SPT results yielded allowable loads of 53.1 tons at BH-3 and 39.0 tons at BH-4, respectively, while laboratory analyses indicated significantly higher bearing capacities of 265.9 tons and 884.4 tons, respectively. Settlement predictions based on SPT and laboratory data were 0.61 cm and 2.07 cm, with an estimated 90% consolidation period of about 12.9 years. These findings emphasize the variability and compressibility of the soft clay strata as well as the importance of employing multiple assessment methods. The study provides essential input for foundation planning and highlights the need for integrated geotechnical assessment methods to ensure the safety, reliability, and long-term performance of pile-supported structures at the proposed port site.